ENT 600 : Life-batt / Puteri Najihah Megat Zakaria, Nurul Izzah Azlan and Erlina Mohamad Jaaper - Megat Zakaria, Puteri Najihah; Azlan, Nurul Izzah; Jaaper, Erlina Mohamad (2018)
The team is developing a device called Life-Batt which enables two phones to share the battery without using a wire or external battery such as power bank. Life-Batt is designed to be compatible with all types of phones. The idea is generated based on the observation of our daily life that shows many people face problem when their phones runs out of battery. Besides, phones battery can last less last than 24 hours. Most people claim that even though they have a portable charger, they sometimes forget to charge the portable charger. Different phones have different charger cable and this causing a problem to most people as they have to bring their own charger cable everywhere they go. As people nowadays prefer a convenient device to make their life easier. Life-Batt is suitable as it is small, wireless, and it is compatible with all types of phones. Target market are students and workers age between 18 to 45 years old. These groups are having users of smart phone.